مياه الفرات في العلاقات السورية التركية - محمود, يوسف; عطية, قصي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لم تعد الحاجة للمياه مقتصرة على الشرب والري فقط بل تطورت إلى مجالات كثيرة كالملاحة والاستخدامات الصناعية وتوليد الطاقة وغيرها , مما جعل مصالح الدول التي تقع على ضفاف الأنهار الدولية المشتركة تتشابك وتتعارض على كميات المياه التي تحتاج إليها من هذه الأنهار , الأمر الذي استدعى نشوء فكرة إيجاد أسس وقواعد جديدة ومشاريع اتفاقيات تنظم كيفية استعمال مياه الأنهار الدولية المشتركة، بحيث تحد من الاستعمالات الضارة والماسة بحقوق الدول المتشاطئة على تلك الأنهار , وتضع القواعد التي تحفظ حقوق كل منها بما لا يتعارض مع المصالح الحيوية وحقوق الدول المتشاطئة الأخرى . The need of water is not limited by drinking and irrigation. It is evolved for navigation and industrial uses, power generation and others. So, this has made the interests of the countries on the shores of world rivers related to the amount of water they need from these rivers. This necessitated finding the idea of creating the foundations of the new rules and agreements organizing the use of waters of those international shared rivers to limit the harmful uses to the rights of States on those rivers, and thus establishing rules to protect these rights without contradiction between vital interests and rights of shared States.